Stranger things. The other side. #2 - Houser, Jody (Spotlight ; Dark Horse Books, 2020)
Comic book adaptation of the Netflix series "Stranger Things," following the story of Will Byers through the first season as he explores the terrors of the Upside Down and tries to find a way back to his mom and friends.